2022
DOI: 10.3390/catal12020218
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Au/ZrO2 Catalysts Prepared via Postsynthesis Methods in CO2 Hydrogenation to Methanol

Abstract: Au nanoparticles supported on ZrO2 enhance its surface acidic/basic properties to produce a high yield of methanol via the hydrogenation of CO2. Amorphous ZrO2-supported 0.5–1 wt.% Au catalysts were synthesized by two methods, namely deposition precipitation (DP) and impregnation (IMP), characterized by a variety of techniques, and evaluated in the process of CO2 hydrogenation to methanol. The DP-method catalysts were highly advantageous over the IMP-method catalyst. The DP method delivered samples with a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 67 publications
(96 reference statements)
0
8
0
Order By: Relevance
“…The formate pathway was determined on an Au/ZrO 2 catalyst prepared by both impregnation and deposition precipitation. 211 A mixed oxide In 2 O 3 –ZrO 2 strongly enhanced the catalytic activities with respect to the Au/In 2 O 3 and Au/ZrO 2 counterparts. This phenomenon was attributed to a reduced activation energy, a stabilization of indium oxide, a higher amount of oxygen vacancies and a superior CO 2 adsorption.…”
Section: Co2 To Methanolmentioning
confidence: 93%
“…The formate pathway was determined on an Au/ZrO 2 catalyst prepared by both impregnation and deposition precipitation. 211 A mixed oxide In 2 O 3 –ZrO 2 strongly enhanced the catalytic activities with respect to the Au/In 2 O 3 and Au/ZrO 2 counterparts. This phenomenon was attributed to a reduced activation energy, a stabilization of indium oxide, a higher amount of oxygen vacancies and a superior CO 2 adsorption.…”
Section: Co2 To Methanolmentioning
confidence: 93%
“…The ZrO 2 -CeO 2 nanocomposites were synthesized following a precipitation method in a previously published work [27] with slight adjustments. Typically, 4 g of zirconium (IV) oxynitrate (ZrO(NO 3 ) 2 ⋅xH 2 O, Sigma Aldrich) and a predetermined amount of cerium (III) nitrate hexahydrate (Ce(NO 3 ) 3 ⋅6H 2 O, Sigma-Aldrich) was dissolved in 50 mL deionized water resulting in an aqueous solution of 0.1 M Zr 4+ and 0.1x M Ce 3+ , respectively, with x denoted for the Ce to Zr molar ratios (x = n Ce /n Zr ).…”
Section: Synthesis Of Zro 2 -Ceo 2 Mixed Oxidesmentioning
confidence: 99%
“…Au-based catalyst is another classic example of the strong dependence between Au particle size and the corresponding catalytic activity [24][25][26]. The highly dispersed Au nanoparticles (≈1 nm) supported on amorphous ZrO 2 via deposition precipitation method provided a much higher methanol formation rate than that of Au/ZrO 2 (d Au ≈50 nm) synthesized by impregnation, i.e., 2.1 > 0.4 g CH3OH • ( g cat • h ) − 1 in the methanol synthesis from CO 2 (240 • C, 40 bar) [27]. It is suggested that the particle size of active metal is strongly associated to the number of interfacial surface area, at which the methanol synthesis has been repeatedly reported to take place [28,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In continuation of the above studies, altering the physicochemical properties of metal oxides (acidity, basicity, oxygen vacancies, and Lewis acid-base pair) has been investigated and found to strongly influence product distribution. [23][24][25][26][27][28][29][30][31][32][33][34] In line with this, Touchy et al 35 developed Mo-promoted Pt-MoO X /TiO 2 for the reductive amination of LA to OMP at 100 °C, 3 bar H 2 , obtaining a near quantitative yield (99%). Vidal et al 36 prepared Pt/TiO 2 via the deposition-precipitation method for the reductive amination of ethyl levulinate, affording a high selectivity towards the target product at 120 °C under solvent-free conditions.…”
Section: Introductionmentioning
confidence: 97%